Phytogeographic characterization of Gran Canaria Island (Canary Islands-Spain) - Salas-Pascual, Marcos; Quintana-Vega, Gregorio; Fernández-Negrín, Emilio (Lazaroa, 2015)
Studies on the flora and fauna of the Canary Islands show that this Archipelago is one of the planet’s diversity hot spots. However, an analysis of the differences in the phytogeographic characteristics of each of the islands that make up this Archipelago is lacking. This article focuses on the phytogeographic characterization of the island of Gran Canaria. This island exhibits geological and climatic characteristics resulting in a rich vascular flora, including endemic species and genera that are significantly different from the other islands of the Archipelago. These differences are verified through statistical analysis of the existing similarity between the floras of the members of the Canary Islands. This study also analyses the subdivision of Gran Canaria Island, indicating that there are three well-differentiated areas on the island itself. Finally, this study argues that these areas, themselves, should be considered biogeographic sectors.